Efektivitas Strategi Pemasaran Online Pada CV. Al-Ahda Medan - Wahyu Akbar Alfarizi (AGHNIYA : Jurnal Ekonomi Islam, 2022)
This study aims to determine the effectiveness and strategies of online marketing in CV. Al-AHDA Medan. This research method uses qualitative methods with data collection techniques through interviews with company owners and company directors. This research was conducted for almost six months, in this study there are several problems that must be resolved, namely, first, the marketing method used by CV. Al-AHDA is less effective, because it only relies on family to family, friend to friend. In addition, the strategies and concepts used, are still conventional, have not upgraded the marketing system like what developing companies have done now. If you don't upgrade the existing marketing system in the company, you will certainly be left behind by other company competitors. During the pandemic, not all of the company's products showed maximum sales.